The indirect method of steganographic embedding of data in an image container based on the information of the contour - Бараннік, В.В.; Шатун, О.М.; Бараннік, Д.В. (Science-based technologies, 2018)
The article discusses issues related to the use of methods of digital steganography for information security in systems of critical appointment. Proposed allocation of sustainable regions in the attacking effects on the basis of the moving mask. Developed an indirect method of steganography is hiding data in blocks which include information about contour.